Avaliação toxicológica subcrônica do consumo de óleo de coco - Amaral, Ariana de Alencar Gonçalves Ferreira do (2013)
Coconut oil obtained from the abundant fruit in northeastern Brazil, is rich in saturated fatty acids, especially lauric acid, and has aroused particular interest in the chemical, pharmaceutical and food industries due to its antiviral, antifungal and bactericidal beyond the antioxidant capacity allocated to the lauric acid and minor components. Despite concerns about the safety of this product for consumption and its impact on cardiovascular disease, studies have shown that consumption of virgin coconut oil, one obtained by extracting the pulp dry, cold pressed, which keeps biologically active components such as vitamin E and polyphenols, presents no health risks. Its fatty acid composition of medium chain has made significant use in the treatment of obesity, absorptive disorders related to the consumption of long-chain fatty acids, and yet, in ketogenic diet for patients with drug-resistant epilepsy. To contribute to the discussion of the problem, this work presents two main sections: a literature review chapter, with key nutritional and therapeutic uses of coconut oil, demonstrating its promising use in the treatment of various disorders, and article results as regards the experimental study with rats weaned, which received standard diet, a diet based on coconut oil or ketogenic diets based on soybean oil or coconut oil. The rats receiving diets regulate lipid concentration showed greater weight gain than the ketogenic groups, independent of lipid source, which in turn, exhibited significantly lower serum triglycerides, total cholesterol and LDL + VLDL compared to animals control. Histological analysis revealed less than half the number of cases of hepatic steatosis in animals fed the ketogenic diet based on soya bean oil and coconut oil, as well as severity smaller than those subjected to the standard diet. Variables such as weight gain, total cholesterol and LDL + VLDL showed potential protective effect of coconut oil. This effect, coupled with clinical evidence of successful use of coconut oil in some metabolic disorders, arouses interest in future investigations of its therapeutic application in other disorders.